1990
DOI: 10.1007/bf02253712
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide substance P improves water maze performance in aged rats

Abstract: The effects of the peripherally administered neuropeptide substance P (SP) on spatial learning capacities were investigated in 27-month-old rats using a water-maze task. Old rats were injected intraperitoneally once daily for 6 days with 50 or 250 micrograms/kg SP or vehicle 30 min prior to acquisition trials. Improvement in maze performance was observed following injections of 250 micrograms/kg SP only. Furthermore, vehicle-treated old rats showed significantly poorer acquisition rates than vehicle-treated 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…However, it is possible that the memory-facilitating effect of SP is not solely modulated by NK1-Rs on cholinergic neurons, but also by NK3-Rs, because SP, although with highest affinity to NK1-Rs, can also bind to NK3-Rs (9,29). Our current finding of memory facilitation via NK3-R activation by senktide and the consequential increase of ACh release might also account for previously described memory-promoting effects of SP in aged animals (26).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, it is possible that the memory-facilitating effect of SP is not solely modulated by NK1-Rs on cholinergic neurons, but also by NK3-Rs, because SP, although with highest affinity to NK1-Rs, can also bind to NK3-Rs (9,29). Our current finding of memory facilitation via NK3-R activation by senktide and the consequential increase of ACh release might also account for previously described memory-promoting effects of SP in aged animals (26).…”
Section: Discussionsupporting
confidence: 72%
“…Aged humans and animals show considerable individual differences in performance in cognitive tasks (21,22,26,27). Ageassociated differences in sensitivity to NK3-R agonism most likely reflect differences in cholinergic degeneration (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, deficiencies in substance P and vasopressin have been reported in postmortem studies of cerebral tissue derived from patients with neurodegenerative diseases (Ferrier et al 1983;Rossor et al 1986;Beal and Mazurek 1987;Husain and Nemeroff 1990). Hence, peptidergic alterations might play a significant role in age-related cognitive decline.This suggestion is further supported by evidence for a beneficial effect on mnemonic performance following substance P treatment in aged rats (Hasenöhrl et al 1990). A similar facilitation has also been seen in patients with Alzheimer's disease following TRH treatment (Mellow et al 1989(Mellow et al ,1993Molchan et al 1992) and in volunteer subjects treated with scopolamine (Molchan et al 1990(Molchan et al ,1992.…”
mentioning
confidence: 60%
“…This suggestion is further supported by evidence for a beneficial effect on mnemonic performance following substance P treatment in aged rats (Hasenöhrl et al 1990). A similar facilitation has also been seen in patients with Alzheimer's disease following TRH treatment (Mellow et al 1989(Mellow et al ,1993Molchan et al 1992) and in volunteer subjects treated with scopolamine (Molchan et al 1990(Molchan et al ,1992.…”
mentioning
confidence: 60%
“…Administration of SP has also been reported to improve passive and active avoidance performance (Pelleymounter et al 1986;Schlesinger et al 1983) and ICV administration of NKA enhances T-maze learning (Flood et al 1990). Systemic administration of SP has also been demonstrated to counteract age-related learning deficits (Hasenohrl et al 1990(Hasenohrl et al , 1994. In addition, SPfragment studies have demonstrated that the effects of SP seem to be encoded by different SP-sequences with the Nterminal SP1-7 enhancing memory, while the C-terminal heptapeptide and hexapeptide sequences of SP appear to mediate its reinforcing properties (Huston and Hasenohrl 1995).…”
Section: Discussionmentioning
confidence: 98%